2021
DOI: 10.2147/ccid.s322859
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Media and Photo-Editing Practice on Seeking Cosmetic Dermatology Care

Abstract: Background The use of social media and photo-editing practice has grown enormously over the past decades. Photo editing can alter a person’s desire to look better in photographs posted on social media platforms. Objective To assess the cosmetic dermatology seeking behavior of social media users and those who edit photographs before posting them on social media platforms. Methods A validated self-administered structured questionnaire via Googl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 14 publications
5
18
0
1
Order By: Relevance
“…The study observed that hiding skin lesions like, acne or acne scar, pigmentation, and dark circles were the most common reason for editing a photograph. Additionally, fifty percent of participants were dependent on appearance and had untagged themselves or removed a photo from social media when the photo was not digitally enhanced or edited to their liking [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study observed that hiding skin lesions like, acne or acne scar, pigmentation, and dark circles were the most common reason for editing a photograph. Additionally, fifty percent of participants were dependent on appearance and had untagged themselves or removed a photo from social media when the photo was not digitally enhanced or edited to their liking [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the modernized world, there have been so many photo editing applications launched which have allowed young people to enhance their effects. Out of all social media platforms, Facebook users account for about (86.4%) followed by YouTube (82%) and Instagram (81.1%) [12]. People have used social media in order to create awareness and motivation related to cosmetic dermatology care.…”
Section: Impact Of Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Dengan demikian pengguna juga dapat mengembangkan keterampilan mereka dalam menggunakan kamera dan juga meningkatkan permintaan pasar untuk produksi aplikasi seluler untuk pemrosesan foto digital [2]. Unggahan paling banyak ditemukan di media sosial, facebook dan instagram paling banyak dilakukan oleh pengguna smartphone untuk mengunggah hasil pengambilan gambarnya [3]. Selain itu, smartphone menyediakan aplikasi untuk editing foto yang jumlahnya lebih banyak dibandingan dengan kamera digital.…”
Section: Pendahuluanunclassified
“…78 The rest of the studies reviewed indirectly express the role of men with the word beauty, such as have a clear looking or beautiful skin or looking young or fresher. 47,55,64 Other reasons are to look better, prettier, or more attractive to oneself. 55,64 Although the narrative is self-directed, the theory of sexual selection emphasizes that this is a sexual signal to the opposite sex.…”
Section: Dovepressmentioning
confidence: 99%